False Testimony and Oath: Reopening a Legal Case in Iranian Courts - Zeajeldi, Iman; Parhammeh, Hamid Reza; Taram, Maysam (Journal of History Culture and Art Research, 2017)
In Iranian legal laws, hearing a case ends by issuing the final judgment. However, the law has provided conditions where the individuals can apply for retrial so that their rights will be protected and losses will be prevented. This means that court will rehear a case for which it has issued a final judgment. Now, each of the parties to the claim who has applied for reopening must prove the conditions of reopening. One of the conditions is proving the falsehood in the claim. Yet, the question is ‘under which conditions the falsehood brings about the annulment of the judgment issued’. The present research aims to study the effects of falsehood cases in the possibility of applying for reopening and annulling the judgment issued.